Parque Vereda del Lago: reconfigurando los límites del espacio público - Astrid Petzold-Rodríguez (Confins)
This work seeks to demonstrate, through the analysis of the ways of appropriation and use of the Vereda del Lago Park (1976-78), Maracaibo, Venezuela, i) the existence of tangible and intangible limits, and ii) how the predominant social groups in the park, and the public institutions in charge of it, try to regulate the behaviors of the people in the park.The key concepts of living, appropriation and use are used to approach, from a practical point of view, the study of practices, and show the ways in which these practices subvert the design of the place, as well as reveal the conflicts that occur in this space, when transgressing established standards. The observational work and the analysis of the interviews carried out revealed that the Vereda del Lago Park is a public space contested in certain periods of time and in certain areas, and in continuous reconfiguration of the limits of what is considered public